A Stress and Resilience Among Adolescents Experiencing Unintended Pregnancy: A Scoping Review - Raodiatul Jumiati; Andari Wuri Astuti; Mohammad Hakimi (Masters Program in Public Health, 2025)
Background: Unintended pregnancy (UP) among adolescents represents a global issue with profound psychological, social, and emotional consequences. Adolescents experiencing UP often face social stigma, family pressure, and uncertainty about their future, which can lead to prolonged psychological distress. This study aims to explore the experiences of stress and the resilience strategies employed by adolescents dealing with UP.Subjects and Method: This research employs a scoping review methodology based on the Arksey and O’Malley framework, with the population consisting of adolescents, teenage girls, and young mothers. The concepts included stress, stress experience, resilience strategies, and coping mechanisms, and the context was applicable across various settings. Literature was sourced from databases such as PubMed and ScienceDirect. Inclusion criteria comprised scholarly publications in English or Indonesian, primary research articles or relevant reviews addressing similar themes, and studies published within the last 10 years to ensure relevance. The PRISMA Flowchart illustrated the selection process, while the critical appraisal of the selected articles followed the Joanna Briggs Institute (JBI) guidelines.Results: UP is a significant contributor to psychological stress among adolescents, driven by social stigma, isolation, and a lack of emotional support. Nevertheless, resilience emerges as a crucial factor in managing such stress. Protective factors such as support from family and peers and emotional regulation training are pivotal in enhancing adolescent resilience.Conclusion: Community-based interventions focusing on fostering resilience through the development of psychological skills and stress management strategies are essential for supporting the mental health of pregnant adolescents.